2008
DOI: 10.1097/tp.0b013e3181734995
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Short Bowel Syndrome Acquired Early in Life and During Adolescence

Abstract: Acknowledging the inherent biases created in defining the two groups, pediatric patients developing SBS early in life seem to be similar to those who develop SBS as adolescents with regards to long-term outcome, despite differences in origin and intestinal anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…A study of a cohort of adolescents with SBS, where no HPN-related death was observed during a follow-up of several years supports that observation. 59 7,22,29,65,67e69,71 In patients with PDI, the cause of death was related to the underlying disease 7,57 or to HPN. 22 The underlying disease was the main cause of death in patients with IF due to primary non-digestive disease.…”
Section: Patient Populationmentioning
confidence: 98%
“…A study of a cohort of adolescents with SBS, where no HPN-related death was observed during a follow-up of several years supports that observation. 59 7,22,29,65,67e69,71 In patients with PDI, the cause of death was related to the underlying disease 7,57 or to HPN. 22 The underlying disease was the main cause of death in patients with IF due to primary non-digestive disease.…”
Section: Patient Populationmentioning
confidence: 98%
“…Whether resulting from congenital causes or occurring following any extensive surgical small bowel resection, once a patient is left with less than 180 cm of small bowel, they are at significant risk of developing SBS [9] . To date, there have been numerous procedures described to surgically alleviate SBS, including intestinal transplantation, as well as other nontransplant bowel-lengthening procedures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital SBS also occurs. In older children, trauma, postoperative SBS, and malignancies become important reasons for resection [ 10 ]. Motility disorders requiring resection are also potential mechanisms for SBS in both infants and children.…”
Section: Causes Of the Short Bowel Syndromementioning
confidence: 99%